On the Relationship of Annual Variations of the Intensity of Galactic Cosmic Rays with the Variability of Total Cloudiness, Atmospheric Precipitation and Air Temperature in Tbilisi in 1966-2015 - G. Amiranashvili, Avtandil; S. Bakradze, Teimuraz; G. Erkomaishvili, Tereza; Ya. Ghlonti, Nugzar; I. Tuskia, Irakli (Journals of Georgian Geophysical Society, 2020)
The paper considers the results of the study of the connection between annual variations of intensity of galactic cosmic rays and the changeability of the total cloudiness, atmospheric precipitation and air temperature in 1966-2015 in Tbilisi. The statistical characteristics of the indicated parameters (trends, random component, linear correlations between real and random components, etc.) are studied. In particular, it was found that, within the variation range, the contribution of the studied parameters to atmospheric precipitation variability is as follows: total cloudiness - 17.1%, real values and random components of cosmic ray intensity - 37.8% and 28.0%, respectively.